2007
DOI: 10.1021/ic0618706
|View full text |Cite
|
Sign up to set email alerts
|

Chelate Control of Diiron(I) Dithiolates Relevant to the [Fe−Fe]- Hydrogenase Active Site

Abstract: The reaction of Fe 2 (S 2 C 2 H 4)(CO) 6 with cis-Ph 2 PCH=CHPPh 2 (dppv) yields Fe 2 (S 2 C 2 H 4) (CO) 4 (dppv), 1(CO) 4 , wherein the dppv ligand is chelated to a single iron center. NMR analysis indicates that in 1(CO) 4 , the dppv ligand spans axial and basal coordination sites. In addition to the axial-basal isomer, the 1,3-propanedithiolate and azadithiolate derivatives exist as dibasal isomers. Density functional theory (DFT) calculations indicate that the axial-basal isomer is destabilized by nonbondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
189
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(206 citation statements)
references
References 28 publications
16
189
0
1
Order By: Relevance
“…The "proximal" {Fe(CO) 2 (PMe 3 )} moiety remains relatively unperturbed, and overall the bond lengths match those in 1 within 0.02 Å. [7] The unique CO ligand is only partially bridging, with a relatively long Fe prox -C separation of 2.62 Å compared to the Fe dist -CO bond length of 1.781(3) Å (∢(Fe dist -C-O) = 170.2(3)°; Figure 1). We have recently described [Fe 2 -(S 2 C 2 H 4 )(CO)(μ-COAX 3 )(dppv) 2 ] (AX 3 = AlBr 3 , B(C 6 F 5 ) 3 ), which is not mixed-valence but also adopts the rotated structure.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The "proximal" {Fe(CO) 2 (PMe 3 )} moiety remains relatively unperturbed, and overall the bond lengths match those in 1 within 0.02 Å. [7] The unique CO ligand is only partially bridging, with a relatively long Fe prox -C separation of 2.62 Å compared to the Fe dist -CO bond length of 1.781(3) Å (∢(Fe dist -C-O) = 170.2(3)°; Figure 1). We have recently described [Fe 2 -(S 2 C 2 H 4 )(CO)(μ-COAX 3 )(dppv) 2 ] (AX 3 = AlBr 3 , B(C 6 F 5 ) 3 ), which is not mixed-valence but also adopts the rotated structure.…”
mentioning
confidence: 90%
“…[6] Our recently reported species [Fe 2 (S 2 C 2 H 4 )(CO) 3 (PMe 3 )-(dppv)] (1, dppv =cis-1,2-C 2 H 2 (PPh 2 ) 2 ) is attractive, because, like the active site, this diiron framework bears three donor ligands and three CO ligands. [7] We previously showed that oxidation of 1 in MeCN gives [1 (NCMe) The purple-colored compound 1-BF 4 is stable in solution for several minutes at room temperature and is sufficiently stable that we were able to grow single crystals for X-ray diffraction (see below). The X-band EPR spectrum of polycrystalline 1-BF 4 (15 K) displays g values at 2.14, 2.03, 2.01 as well as a signal for an apparent impurity at g =2.05; this rhombic pattern is similar to that seen for H ox from D. desulfuricans (g =2.10, 2.04, 1.99).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[6] Our recently reported species [Fe 2 (S 2 C 2 H 4 )(CO) 3 (PMe 3 )-(dppv)] (1, dppv = cis-1,2-C 2 H 2 (PPh 2 ) 2 ) is attractive, because, like the active site, this diiron framework bears three donor ligands and three CO ligands. [7] We previously showed that oxidation of 1 in The purple-colored compound 1-BF 4 is stable in solution for several minutes at room temperature and is sufficiently stable that we were able to grow single crystals for X-ray diffraction (see below). The X-band EPR spectrum of polycrystalline 1-BF 4 (15 K) displays g values at 2.14, 2.03, 2.01 as well as a signal for an apparent impurity at g = 2.05; this rhombic pattern is similar to that seen for H ox from D. desulfuricans (g = 2.10, 2.04, 1.99).…”
mentioning
confidence: 86%
“…The "proximal" {Fe(CO) 2 (PMe 3 )} moiety remains relatively unperturbed, and overall the bond lengths match those in 1 within 0.02 . [7] The unique CO ligand is only partially bridging, with a relatively long Fe prox À C separation of 2.62 compared to the Fe dist À CO bond length of 1.781(3) (a(Fe dist -C-O) = 170.2(3)8; Figure 1). We have recently described [Fe 2 -(S 2 C 2 H 4 )(CO)(m-COAX 3 )(dppv) 2 ] (AX 3 = AlBr 3 , B(C 6 F 5 ) 3 ), which is not mixed-valence but also adopts the rotated structure.…”
mentioning
confidence: 99%